2020
DOI: 10.3390/ani10040689
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in NLRP5 and NLRP9 Are Associated with Litter Size in Small Tail Han Sheep

Abstract: Simple Summary:The NLR family pyrin domain-containing 5 (NLRP5) and NLRP9 genes are two important reproductive genes; however, their effects on litter size in sheep are unknown. In this study, we conducted population genetic and association analyses on five NLRP5 and NLRP9 loci of sheep. Our results suggested that a mutation in g.60495363G > A may decrease interactions of NLRP5 with proteins, such as the growth differentiation factor 9 (GDF9), whereas a mutation in g. g.59030623T > C may enhance the NLRP9-comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Most importantly, FecB has a dosage effect, which indicated that ewes with one copy of the FecB mutation could increase litter size by 1, while two copies of this mutations could significantly increase litter size by 1.5 [ 15 ]. Further studies suggested that SNPs in fecundity genes, such as the growth differentiation factor 9 [ 16 ], bone morphogenetic protein 15 (BMP15) [ 17 ], BMP2 , BMP7 [ 18 ], the NLR family pyrin domain-containing 5 ( NLRP5 ) and NLRP9 [ 19 ], were highly associated with litter size in sheep. Regarding indels, RNA-seq can be an effective method to detect indels as demonstrated by different bioinformatics strategies in many fields such as clinical decision-making [ 20 ], and many studies also found their key roles in litter size.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, FecB has a dosage effect, which indicated that ewes with one copy of the FecB mutation could increase litter size by 1, while two copies of this mutations could significantly increase litter size by 1.5 [ 15 ]. Further studies suggested that SNPs in fecundity genes, such as the growth differentiation factor 9 [ 16 ], bone morphogenetic protein 15 (BMP15) [ 17 ], BMP2 , BMP7 [ 18 ], the NLR family pyrin domain-containing 5 ( NLRP5 ) and NLRP9 [ 19 ], were highly associated with litter size in sheep. Regarding indels, RNA-seq can be an effective method to detect indels as demonstrated by different bioinformatics strategies in many fields such as clinical decision-making [ 20 ], and many studies also found their key roles in litter size.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, all the variants in mRNA can affect stability due to the mRNA secondary structure and free energy [ 30 , 31 ]. However, the functional mechanisms underlying the associations are largely unknown [ 32 , 33 , 34 ]. To more clearly and comprehensively reveal the complex connections between the four haplotypes and miR-184, luciferase assay was performed to investigate the influence of the functional SNP loci.…”
Section: Discussionmentioning
confidence: 99%
“…It is a pity that targeting miR-184 was not a mechanism of the functional SNPs in NY cattle PSAP 3’ UTR. Compared with the expression of miRNA in muscle and adipose, its expression was not sufficient to mediate such a large effect on the morphological traits in NY cattle [ 34 , 35 ]. However, we found an unexpected phenomenon that the luciferase activity of the ACATG and GCGTG group was higher than the GTACA and GTACG group.…”
Section: Discussionmentioning
confidence: 99%